Synthetic Approaches for C-N Bonds by TiO2 Photocatalysis - Ma, Dongge; Zhai, Shan; Wang, Yi; Liu, Anan; Chen, Chuncheng (Frontiers in Chemistry, 2019)
Nitrogen-containing organic compounds possess the most important status in drug 13 molecules and agricultural chemicals. More than 80% currently used drugs have at least a C-N bond. 14 The green and mild methodology to prepare diverse C-N bonds to replace traditional harsh 15 preparation protocols is always a hotspot in modern synthetic chemistry. TiO2-based nanomaterials, 16 considered as environmentally benign, stable and powerful photocatalysts, have recently been applied 17 in some certain challenging organic synthesis including construction of useful C-N compounds under 18 mild conditions that are impossible to complete by conventional catalysis. This minireview would 19 present state-of-the-art paragon examples of TiO2 photocatalyzed C-N bond formations. The 20 discussion would be divided into two main sections: (1) N-alkylation of amines and (2) C-N 21 formation in heterocycle synthesis. Especially, the mechanism of TiO2 photocatalytic C-N bond 22 formation through activating alcohol into C=O by photo-induced hole followed by C=NH-R 23 formation and finally hydrogenating C=NH-R into C-N bonds by combination of photo-induced 24 electron/H+ assisted with loaded-Pt would be covered in detail. We believe that the mini-review will 25 bring new insights into TiO2 photocatalysis applied to construct challenging organic compounds 26 through enabling photo-induced hole and electron in a concerted way on coupling two substrate 27 molecules together with respect to their conventionally independent catalysis behavior.